Book Review: Reid, H. 2014: Climate Change and Human Development. (October 2017) - Tebboth, Mark
Reid, H. 2014: Climate Change and Human Development . London: Zed Books. X + 287 pp. £70 (Hardback), £23.99 (Paperback). ISBN: 978 1 78032 441 8 (Hardback), ISBN: 978 1 78032 440 1 (Paperback).